Innovative Approaches in Secondary School Art Education: Enhancing Student Creativity and Engagement - Aminova Sabina Anvar qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores innovative teaching approaches in secondary school art education aimed at enhancing student creativity, engagement, and artistic competence. It examines interactive teaching methods, project-based learning, flipped classroom strategies, and technology integration as key tools for promoting active, student-centered learning. The study emphasizes practical applications and the benefits of these strategies for fostering technical skills, critical thinking, and personal growth.